Soldado del asfalto :Estudio sobre la construcción de la identidad Skinhead en jóvenes de la ciudad de Quito - Vaca Mejía, Paúl Emigdio (2016)
Young people in their quest to differentiate themselves were created in England in the late 1970s the skinhead identity. Its aesthetics and aggressive behaviors are the mixture of the practices of young Englishmen of Jamaican origin called rude boys and the British mod. The removal of the majority of those who originally formed the proletarian was skinhead identity. The skinhead movements are attributed to them, social prejudices generated by the groupings skin NS (National Socialists) which are assumed as nationalistic, racist and xenophobic. For this reason appear, in the 1980s, ramifications of the grouping antagonistic skinhead NS, they are called SHARP (Skinheads Against Racial Prejudice) and RASH (Red and Anarchist Skinhead). The skinhead phenomenon arrived to Ecuador in the end in 1980s. In 1989 is created in Quito the Blood X Blood grouping, the first grouping of skinhead of the country. Then appear in the city other groupings that are identified as skinheads, some in the line of the National Socialist and other opposite to this political stance. The different skinhead groupings that exist in Quito, between 1989 and 2011, are hermetic societies; women and men who practice martial arts, exercise violence and take pride in promoting ingroups principles both ethical and moral: justice, honesty, solidarity, loyalty. We can place these groupings skinheads in several areas of the capital's geography, being the most representative places to the north, San Carlos, Mitad del Mundo, Central University sector; to the south Camal sector and areas surrounding the Pasteurizadora Quito. In 2012 we find the second generation of skinheads of Quito, who assume the identity of skinhead with similar positions to the first generation, but with special emphasis on their violent practices as evidence of identity ascription skin.